Surveillance on the sensitivity of various clinical isolates to cefditoren - Ikeno, Hiroyuki; Yokozawa, Mitsuhiro; Sano, Kazumitsu (Japanese Journal of Chemotherapy, 1999)
The change in the sensitivity of clinical isolates to cefditoren (CDTR) was investigated by collecting samples in two surveys. In the first survey, 23 species including 805 strains which were isolated from clinical materials during the 3 month period from April to June 1995 were collected for measurement as test strains. Furthermore, 24 species including 803 strains collected during the one year period from July 1996 to June 1997, were used as the test strains in the second survey. The MIC distribution of CDTR in each test strain that was isolated at the time of the second survey demonstrated a tendency similar to that observed in the test strains isolated for the first survey. However, the MIC80 values in Streptococcus pneumoniae, Proteus mirabilis, Providencia rettgeri and Morganella morganii were 4 to 8 times higher in the second survey, compared to the first survey. Of the strains collected during the second survey, CDTR demonstrated strong antibiotic action against 5 major species which cause respiratory. infections (methicillin susceptible Staphylococcus aureus, Streptococcus pyogenes, S. pneumoniae, Haemophilus influenzae, Moraxella catarrhalis). Furthermore, CDTR inhibited the growth of all the strains of H. influenzae, S. pyogenes, S. pneumoniae, S. aureus and M. catarrhalis at MICs of 0.05, 0.1, 0.39, 0.78 and 0.78μg/ml respectively. The above results coincide with those reported by each medical institution during the development stage of this drug.